Too many crying babies: a systematic review of pain management practices during immunizations on YouTube - Harrison, Denise; Sampson, Margaret; Reszel, Jessica; Abdulla, Koowsar; Barrowman, Nick; Cumber, Jordi; Fuller, Ann; Li, Claudia; Nicholls, Stuart; Pound, Catherine M (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background Early childhood immunizations, although vital for preventative health, are painful and too often lead to fear of needles. Effective pain management strategies during infant immunizations include breastfeeding, sweet solutions, and upright front-to-front holding. However, it is unknown how often these strategies are used in clinical practice. We aimed to review the content of YouTube videos showing infants being immunized to ascertain parents’ and health care professionals’ use of pain management strategies, as well as to assess infants’ pain and distress. Methods A systematic review of YouTube videos showing intramuscular injections in infants less than 12 months was completed using the search terms "baby injection" and "baby vaccine" to assess (1) the use of pain management strategies and (2) infant pain and distress. Pain was assessed by crying duration and pain scores using the FLACC (Face, Legs, Activity, Cry, Consolability) tool. Results A total of 142 videos were included and coded by two trained individual viewers. Most infants received one injection (range of one to six). Almost all (94%) infants cried before or during the injections for a median of 33 seconds (IQR = 39), up to 146 seconds. FLACC scores during the immunizations were high, with a median of 10 (IQR = 3). No videos showed breastfeeding or the use of sucrose/sweet solutions during the injection(s), and only four (3%) videos showed the infants being held in a front-to-front position during the injections. Distraction using talking or singing was the most commonly used (66%) pain management strategy. Conclusions YouTube videos of infants being immunized showed that infants were highly distressed during the procedures. There was no use of breastfeeding or sweet solutions and limited use of upright or front-to-front holding during the injections. This systematic review will be used as a baseline to evaluate the impact of future knowledge translation interventions using YouTube to improve pain management practices for infant immunizations.